Thrombectomy in Acute Ischemic Stroke: Challenges to Procedural Success - Yoo, Albert J.; Andersson, Tommy (Journal of stroke, 2017)
The overwhelming clinical benefit of intra-arterial stroke therapy owes to the major advance in revascularization brought on by the current generation of thrombectomy devices. Nevertheless, there remains a sizeable proportion of patients for whom substantial reperfusion cannot be achieved or is achieved too late. This article addresses the persistent challenges that face neurointerventionists and reviews technical refinements that may help to mitigate these obstacles to procedural success. Insights from in vitro modeling and clinical research are organized around a conceptual framework that examines the interaction between the device, the thrombus and the vessel wall.